The status of Belinuropsis wigudensis Matthew, 1910, a Pennsylvanian merostome from New Brunswick, Canada - Miller, Randall (Atlantic Geology, 1995)
Fossils comprising the type specimen of the merostome Belinuropsis wigudensis Matthew, 1910 have been located in the New Brunswick Museum collection. The specimens raise questions concerning the validity of the monotypic genus Belinuropsis.